THE EFFECTIVENESS OF USING PHOTOGRAPHS ON TEACHING WRITING NARRATIVE TEXT FOR NON-ENGLISH DEPARTMENT STUDENTS - Fitrana Harintama (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2018)
This study concerns about teaching writing, especially writing narrative text by using picture prompts as media. Picture prompts are believed can make the students relax to study and can encourage them to begin to write. Picture prompts have many advantages in teaching and learning writing. Related to the objective of the study, the aim of this study is to find whether picture prompts can help the students to get higher scores or not. This research will be done in UIN Maulana Malik Ibrahim Malang in Arabic Language and Literature Department with the research object of class A for experimental group and class B for control group. The objective of the study is to investigate the effectiveness of using picture prompts in writing class in helping students write narrative texts. The quasi-experimental research design will be used in writing this research. This research design was chosen because it was impossible for the researcher to randomize the subjects to the intended conditions. This was due to the fact that moving the students from one class to another in order to get the ideal groups for the sake of the experiment was not allowed. As the study deals with the students of two different classes, the explanation about teaching-learning processes will be applied to it. In the processes, the researcher will conduct pretest to know the students’ writing ability before getting treatment of writing narrative using picture prompts. After the treatment, the researcher conducts posttest to compare the result and to discover whether the students get higher score or not. Then the results of the research between two subjects will be analyzed using SPSS (Statistical Package for The Social Science) data analysis of group pair data. Keywords: Picture Prompts, Narrative Text, Writing